A Multimodal Protocol to Limit Opioid Exposure and Effectively Manage Postoperative Cesarean Birth Pain. Issue 2 (March 2023) - Harden, Ronda; Dawkins, Denise; Stallings-Saints, Keya; Hampton, Michelle DeCoux; DeLilly, Carol
Abstract: Purpose: To evaluate the impact of implementing a multimodal plan of care in treating the pain of the postoperative cesarean birth patient that limited opioid exposure. Study Design and Methods: A retrospective medical record review was conducted to evaluate a pain management protocol implemented for postoperative cesarean patients before and after a practice change. Sample included term postoperative cesarean patients ≥ 37 weeks of gestation, who had spinal or epidural, were 18 years or older, gave birth to a singleton newborn, admitted to the maternal child health department, and were prescribed opioids as a postoperative pain management treatment plan. Participants ( N = 150) were evaluated based on two groups: n = 75 in the preimplementation group and n = 75 in the postimplementation group. Results: There was a significant difference in the total oral opioid milligrams administered between the pregroup ( M = 27.13) and postgroup ( M = 8.43), after the practice change ( p < .001). There was an increase of nonopioids administered to treat and manage postoperative cesarean pain, Motrin PO ( p = < .001) and Tylenol PO ( p = .002). Clinical Implications: Fewer milligram equivalents of morphine were administered when postoperative cesarean patients were placed on scheduled nonopioids to treat pain. Abstract : Implementation of a multimodal protocol to manage post-operative cesarean birth pain during the postpartum hospitalization was associated with decreased use of opioids among patients who had a cesarean birth compared with patients who had a cesarean birth before the protocol was in place.